The Wenchuan Earthquake of 2008 Anatomy of a Disaster - Yong, Chen.; Booth, David C.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
"The Wenchuan Earthquake of 2008: An anatomy of disaster" gives a detailed account of the damage, seismology and tectonics of the event and discusses earthquake prediction, seismic hazard and risk management, the creation and implementation of building codes, and new practices used in rescue, relief and reconstruction. It will be of significant interest to researchers and practitioners engaged in seismology, geophysics, engineering, the social sciences, and disaster management and recovery. It also offers a valuable new and uniquely Chinese perspective with many insights for future mitigation of earthquake risk. Professor Yong Chen works for the China Earthquake Administration; Dr David C. Booth works for the British Geological Survey.
Wenchuan earthquake -- Wenchuan earthquake:Seismological features -- Prediction efforts prior to Wenchuan earthquake -- Seismic Hazard Assessment -- Emergency response and Rescue -- Reconstruction of Wenchuan.
Keywords: Earth sciences; Natural disasters; Geotechnical engineering; Physical geography; Engineering geology; Engineering -- Geology; Foundations; Hydraulics; Environmental management; Earth Sciences; Natural Hazards; Geotechnical Engineering & Applied Earth Sciences; Geoengineering, Foundations, Hydraulics; Environmental Management; Physical Geography; Electronic books